Conduta da guerra na era digital e suas implicaç\~oes para o Brasil: Uma análise de conceitos, políticas e práticas de defesa - Érico Esteves Duarte (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This report aims to foster the Brazilian public debate on national defense by introducing a study on the impacts of digitalization of warfare in the organization of relevant national armed forces and their implication on Brazil. First, it assesses conceptual backgrounds on military technology and points out in favor of Clausewitz's theory of war. Second, it distinguishes practices and policies on digitalization of war by the United States, Russia, China and Israel, especially in regard of unmanned aerial system (UAS), direct energy weapons (DEW) and guided missiles for coastal defense. Third, it contrasts these overall previous findings with Brazilian strategic context of limited wars and its practices and policies on national defense. Finally, this study closes with some recommendations.
Keywords: O33; 330; Defense Policy; Military Technology; Digitalization of Warfare; Revolution in Military Affairs; Fourth Generation Warfare; Strategic Studies